Desenvolvimento de um sistema microcontrolado de baixo custo utilizando smartphone para aplicações de automação residencial - Sartori, Guilherme (2015)
This work conducts studies about domotic using electronics systems for residential application. It also describes the development method of a low cost home automation system, through smartphones and Arduino, ensuring comfort, safety and well-being of the user in daily activities, considering economic aspects and simplicity. Designed for web, the program assures compatibility on most operating systems and simple and friendly interface.